The Importance of Being Profiled: Improving Drug Candidate Safety and Efficacy Using Ion Channel Profiling - Kaczorowski, Gregory J.; Garcia, Maria L.; Bode, Jacob; Hess, Stephen D.; Patel, Umesh A. (Frontiers in Pharmacology, 2011)
Profiling of putative lead compounds against a representative panel of relevant enzymes, receptors, ion channels and transporters is a pragmatic approach to establish a preliminary view of potential issues that might later hamper development. An early idea of which off-target activities must be minimized can save valuable time and money during the preclinical lead optimization phase if pivotal questions are asked beyond the usual profiling at hERG. The best data for critical evaluation of activity at ion channels is obtained using functional assays, since binding assays cannot detect all interactions and do not provide information on whether the interaction is that of an agonist, antagonist, or allosteric modulator. For ion channels present in human cardiac muscle, depending on the required throughput, manual- or automated- patch-clamp methodologies can be easily used to evaluate compounds individually to accurately reveal any potential liabilities. The issue of expanding screening capacity against a cardiac panel has recently been addressed by developing a series of robust, high-throughput, cell-based counter-screening assays employing fluorescence-based readouts. Similar assay development approaches can be used to configure panels of efficacy assays that can be used to assess selectivity within a family of related ion channels, such as Nav1.X channels. This overview discusses the benefits of in vitro assays, specific decision points where profiling can be of immediate benefit, and highlights the development and validation of patch-clamp and fluorescence-based profiling assays for ion channels.